Credibility of the Interwar Gold Standard, Uncertainty, and the Great Depression - J. Peter Ferderer (Levy Economics Institute of Bard College, 1994)
This paper constructs a theoretical model to show how the credibility of a country s commitment to an international gold standard regime is driven by fundamental determinants such as: 1) shifts in domestic policy, 2) a breakdown in cooperation between central banks, and 3) unilateral devaluations by foreign central banks. Because the credibility of the gold standard regime is an important determinant of domestic interest rate uncertainty, the latter is endogenously linked to changes in the fundamental determinants. Applying this analysis to the inter-war period, the paper shows that GARCH measures of interest rate uncertainty rose dramatically in the U.S. during the early 1930s and that movements in this series can be explained by events which affected the credibility of the U.S. commitment to the gold standard. Also, interest rate uncertainty explains a great deal of the variation in aggregate output and its components during the interwar period. Thus there is evidence that the breakdown in the gold standard contributed to the Great Depression by injecting increased uncertainty into the U.S. economy.
Keywords: E32; E42; E58; F41; F42; 330